2023
DOI: 10.2188/jea.je20200577
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Number of Patients With Mitochondrial Diseases: A Descriptive Study Using a Nationwide Database in Japan

Abstract: Background To provide a better healthcare system for patients with mitochondrial diseases, it is important to understand the basic epidemiology of these conditions, including the number of patients affected. However, little information about them has appeared in Japan to date. Methods To gather data of patients with mitochondrial diseases, we estimated the number of patients with mitochondrial diseases from April 2018 through March 2019 using a national Japanese health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The prevalence reported was 8 in 100,000 in the paediatric population and 5.7 in 100,000 in the general adult population in north-west Spain [9]. Recently, an interesting and extensive epidemiological study of MD patients in Japan was reported [13] in which the authors were able to recruit 3629 patients, estimating a prevalence of 2.9 per 100,000. However, only mtDNA-related diseases were considered, and this would explain the observation that the most susceptible age class was 40-49 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence reported was 8 in 100,000 in the paediatric population and 5.7 in 100,000 in the general adult population in north-west Spain [9]. Recently, an interesting and extensive epidemiological study of MD patients in Japan was reported [13] in which the authors were able to recruit 3629 patients, estimating a prevalence of 2.9 per 100,000. However, only mtDNA-related diseases were considered, and this would explain the observation that the most susceptible age class was 40-49 years.…”
Section: Introductionmentioning
confidence: 99%
“…The description of new genes has also significantly increased [1][2][3]. There are some previous reports about MD prevalence in specific geographic areas of different countries [4][5][6][7][8][9][10][11][12][13]. Overall, a prevalence of 5-15 cases per 100,000 individuals was estimated [2].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, based on several reports, it seems that the number of patients with mitochondrial diseases (caused by mutations in nuclear or mtDNA) in general population could be higher than it was originally estimated. For more details regarding the incidence of mitochondrial disorders, their geographic distribution and other information see Refs [7,[13][14][15][16][17]. More information regarding individual syndromes and deficiencies described above and many others as maternally inherited diabetes and deafness (MIDD), Alpers-Huttenlocher syndrome, Ataxia neuropathy spectrum, chronic progressive external ophthalmoplegia (CPEO), Pearson syndrome, mitochondrial neuro-gastro-intestinal encephalopathy (MNIGE), Sengers syndrome or MEGDEL syndrome can be found in the following reviews: Refs [2,[18][19][20][21].…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%